TMAO is involved in sleep deprivation-induced cognitive dysfunction through regulating astrocytic cholesterol metabolism via SREBP2 - Zhu, Shan; Wang, Yue; Li, Yansong; Li, Na; Zheng, Yige; Li, Qiao; Guo, Hongyan; Sun, Jianyu; Zhai, Qian; Zhu, Yaomin (Frontiers in Molecular Neuroscience, 2024)
Sleep deprivation (SD) contributes to cognitive impairment. Astrocytic cholesterol biosynthesis is crucial for brain cholesterol homeostasis and cognitive function. However, the underlying mechanism of astrocytic cholesterol metabolism in SD-induced cognitive impairment has not been fully explored. Trimethylamine N-oxide (TMAO), a product of liver flavin-containing monooxygenase-3 (FMO3), has been shown to be increased in the urine of sleep-deprived humans and implicated with peripheral cholesterol metabolism. Nevertheless, how TMAO affects brain cholesterol metabolism remains unclear. In our study, increased FMO3 and brain TMAO levels were observed in the SD mice, and elevated levels of TMAO were confirmed to lead to SD-induced cognitive dysfunction. In addition, we found that the expression of sterol regulatory element-binding protein 2 (SREBP2) is decreased in the brain of SD mice, resulting in the reduction in brain cholesterol content, which in turn causes synaptic damage. Moreover, we demonstrated that TMAO inhibits the expression of SREBP2. In contrast, FMO3 inhibitor 3,3′-diindolylmethane (DIM) alleviates SD-induced cognitive impairment by targeting the liver–brain axis. In conclusion, our study revealed that the TMAO pathway is involved in memory impairment in SD mice through deregulating astrocytic cholesterol metabolism.